Pregnancy Following Metabolic–Bariatric Surgery in a Woman With Potential Premature Ovarian Failure: A Case Report - Raheleh Moradi; Maryam Kashanian; Somayeh Mokhber; Abdolreza Pazouki (Case Reports in Surgery)
Premature ovarian insufficiency (POI) is associated with decreased ovulation in the precursor stage which leads to ovarian failure in the end stage. Metabolic–bariatric surgery (MBS) can improve women’s reproductive status, including the release of sex hormones, ovulation, and fertilization. Here, we report a spontaneous pregnancy following MBS despite potential ovarian insufficiency. A 38-year-old woman with severe obesity underwent three cycles of assisted reproduction that were not successful. Oligomenorrhea ≥ 4 months, laboratory indices, and previous poor ovarian response approved the diagnosis of diminished ovarian reserve and could be considered as the precursor stage of POI. Then a gastric bypass was applied, and a spontaneous pregnancy occurred in the 22nd month after surgery, with 45.80% reduction in body mass index. MBS in women with obesity and idiopathic ovarian insufficiency may increase the chance of spontaneous ovulation and successful pregnancy.